Competitive Capabilities and Performance of Small and Medium Manufacturing Enterprises: Empirical Evidence from Southwestern Nigeria - Osuolale, Misbaudeen Olatunde (My University, 2024)
The study examined the effect of competitive capabilities on performance of the selected Small and Medium Manufacturing Enterprises (SMMEs) in Southwestern Nigeria. A survey research design was used for the study. Primary data were collected through the administration of structured questionnaire. The population comprised of the 1,983 registered SMMEs as contained in the directories of Small and Medium Enterprises (SMEs) associations across the six states of Southwestern Nigeria. The study sample of 333 SMMEs in Southwestern Nigeria was determined using Taro Yamane (1967) sampling formula. A multi-stage sampling technique was used for the distribution of the sample size among respondents. In the first stage, a stratified sampling technique was used in which each state in the Southwestern Nigeria represented a stratum. At the second stage, Probability Proportional to Size was used to distribute the sample size among the states. A random sampling was later used at the third stage to select the sample from each state in the region. Data collected were analysed using multiple regression. The result revealed that competitive capabilities including cost, quality, delivery and flexibility had significant effect on performance while the effect of innovation was insignificant. The study therefore concludes that competitive capabilities constructs enhanced the performance of SMMEs in Southwestern Nigeria.
Keywords: Quality; Cost; Flexibility; Delivery; Innovation; Manufacturing; Performance